Understanding the catalytic behaviour of NiM (M = Pt, Ru, Pd) counter electrode electrocatalysts in liquid-junction dye-sensitized solar cells. (1st December 2015) - Yang, Peizhi; Ma, Chunqing; Tang, Qunwei
Graphical abstract: Highlights: Urchin-like NiM (M = Pt, Ru, Pd) CE electrocatalysts are synthesized for DSSCs. A model for I3 − reduction reaction is built. I3 − reduction reaction rate constant of k = 4π Dr aNB is extracted for 0D catalysts. Abstract: Understanding the electrocatalytic behaviours of counter electrode (CE) electrocatalysts favors to tune the sluggish triiodide (I3 − ) reduction kinetics and to compare their catalytic activities. We present here the experimental realization of cost-effective CE electrocatalysts from urchin-like NiM (M = Pt, Ru, Pd) for studying the profounding charge transfer processes without sacrificing photovoltaic performances of DSSCs. Our focus is placed on the systematic studies of catalytic activities along with modeling of I3 − reduction reaction rate constant, extracting k = 4π Dr a NB for zero-dimensional electrocatalysts. The DSSCs yield conversion efficiencies of 9.08%, 7.74%, and 6.86% with NiPt, NiRu, and NiPd CEs, respectively.